In God We Learn? Religions' Universal Messages, Context-Specific Effects, and Minority Status - Pierre-Guillaume Méon; Ilan Tojerow (Institute for the Study of Labor (IZA), 2016)
We study the relationship between major religious denominations and individuals' levels of education, using the World Values Survey. In a first step, running country-by-country regressions, we report first-time evidence that no single denomination has a universal effect on education. Each denomination has a positive and statistically significant effect in some countries, a negative and statistically significant effect in others, and a statistically insignificant effect elsewhere. In a second step, we relate the sign of the impact of a denomination in a country to whether the denomination is a minority in that country. We find that denominations that are a minority in a country are more likely to be associated with a higher level of education, and less likely to be associated with a lower level of education in that country. In both steps, the findings are independent from the specification of the regressions used in the first stage to determine the sign of the impact of denominations on educational outcomes. The finding of the second step is moreover robust to defining minority denominations using various thresholds. It is robust to controlling for whether the denomination is a state religion, for the country's level of democracy, per capita GDP, or level of education, to introducing denomination- and country- fixed effects, and to controlling for the identity of the largest other denomination in the country.
Keywords: I2; O5; Z1; 330; religion; education; minority